Enhancing Chinese EFL Teachers’ Work Engagement: The Role of Self and Collective Efficacy - Ge, Liping (Frontiers in Psychology, 2022)
Teachers’ work engagement is considered an essential component in instruction. Accordingly, the emphasis should be over physical and mental predictors of this construct. In this line, this study investigates the relationship between Chinese English as a Foreign Language (EFL) teachers’ individual self-efficacy, collective efficacy, and work engagement. To this end, 300 Chinese instructors (males = 96, females = 204) from different colleges and universities participated in this study. The questionnaires were distributed among teachers with different educational levels and experiences. Linear multiple regression was used as a measure for data analysis. The findings showed the significant correlations between teachers’ work engagement, self-efficacy, and collective efficacy. Comparing the predictability power, teachers’ self-efficacy (B = 0.57) proved to have a higher index compared to their index of collective efficacy competence (B = 0.22). This study concluded that self-efficacious teachers and teachers who believe in collective efficacy are more engaged in the EFL contexts. Moreover, the study has some pedagogical implications and suggestions for different teacher educators, administrators, and advisors.